A moisture induced self-charging device for energy harvesting and storage. (June 2019) - Luo, Zhiling; Liu, Changhong; Fan, Shoushan
Abstract: Harvesting energy from water movement has aroused extensive and intensive interest because of its great potential in both energy-related field and wearable electronics. In this work, simply bridging two carbon nanotube (CNT) electrodes by HCl/polyvinyl alcohol (PVA) electrolyte gel with CaCl2 in one side, a novel moisture induced self-charging device (MISD) was successfully fabricated. The MISD can be directly charged to 0.348 V in a humid environment without any complex experimental configuration and the harvesting energy can be effectively stored. The self-charging behaviors under various humid conditions have been explored. The self-charging property is based on the automatic electrolyte diffusion, which is driven by water absorption from moisture by CaCl2 . The diffusion can reorient and dislocate conductive ions and induce a potential across the bridge. The application possibility was demonstrated by scaling up MISDs in series to power a timer. Output improvement of a single MISD is also available based on a sandwich like structure, which can reach 0.243 mW cm −2 . Besides its application potential in wearable and smart electronics, the MISD also provides a reference for the novel utilization of moisture in energy harvesting and storage. Graphical abstract: Image 1 Highlights: A device for harvesting and storage energy from moisture based on supercapacitor structures is originally investigated. The self-charging behaviors under various humid conditions and the mechanism have been explored. The self-charging property is based on the automatic electrolyte diffusion driven by water absorption from moisture. The sandwich type device can reach an output 0.243 mW cm −2, 1-3 orders higher than that of similar generators.